Alterations in retinal arteriolar microvascular structure associate with higher treatment burden in patients with diabetic macular oedema: results from a 12‐month prospective clinical trial. Issue 4 (25th October 2019) - Blindbæk, Søren L; Peto, Tunde; Grauslund, Jakob
Abstract: Purpose: This study was based on data from a 12‐month prospective clinical trial and aimed to examine changes in retinal microvascular structure in eyes treated with intravitreal aflibercept in combination with focal/grid laser photocoagulation for diabetic macular oedema (DME). Methods: We included 32 treatment naïve eyes of 22 patients with centre involving DME. The treatment algorithm comprised a loading phase of three monthly injections of aflibercept and focal/grid laser photocoagulation [baseline (BL)‐month 3 (M3)] followed by a pro re nata (PRN) aflibercept phase until month 12 (M12). Eyes were divided into groups with and without need for PRN treatment after loading. Parameters of retinal microvascular structure were measured in 45° optic disc centred fundus images at BL, M3 and M12 using a semi‐automated software (VAMPIRE®, Vessel Assessment and Measurement Platform for Images of the Retina, Universities of Dundee and Edinburgh, UK). Results: A significant decrease in retinal arteriolar calibre was demonstrated at both M3 (−11.2 μ m, p = 0.005) and M12 (−11.5 μ m, p = 0.04) as compared to BL in eyes that needed PRN treatment during follow‐up. In contrast, arteriolar calibre remained unchanged in eyes without need for PRN treatment (M3: −1.6 μ m, p = 0.79 and M12: −7.0 μ m, p = 0.22). For retinal venules, vessel calibre decreased both in eyes with and without need for PRN therapy at M3 (−9.5 μ m, p = 0.01 and −11.6 μ m, p = 0.01) as well as at M12 (−15.6 μ m, p = 0.001 and −11.0 μ m, p = 0.04). Conclusion: Early changes in retinal arteriolar calibre are associated with an increased treatment burden during the first year of DME treatment.